Dexketoprofen Pharmacokinetics is not Significantly Altered by Genetic Polymorphism - Mejía-Abril, Gina; Zubiaur, Pablo; Navares-Gómez, Marcos; Villapalos-García, Gonzalo; Román, Manuel; Ochoa, Dolores; Abad-Santos, Francisco (Frontiers in Pharmacology, 2021)
Dexketoprofen is the (S)-(+)-enantiomer of racemic ketoprofen, a nonsteroidal anti-inflammatory drug (NSAID) used for the management of different types of pain. To the best of our knowledge, no article was published to date on dexketoprofen pharmacogenetics. Thence, in this work, we aimed to explore the influence of sex, race and several single nucleotide polymorphisms (SNPs) in genes encoding metabolizing enzymes (e.g. CYP or UGT) or transporters (e.g., ABC or SLC) in the pharmacokinetics and safety of dexketoprofen to explore whether dosing adjustments based on genetic polymorphism would be beneficial for its prescription. For this regard, 85 healthy volunteers enrolled in three bioequivalence clinical trials were genotyped for 46 SNPs in 14 genes. Women showed lower AUC adjusted by dose/weight (AUC/DW) and higher Vd/F and Cl/F than men (p<0.05 in univariate and multivariate analysis). CYP1A2*1B allele, CYP2B6 IM/PM and CYP2D6 IM/PM phenotypes were related to drug accumulation (AUC/DW or Cmax/DW) compared to the CYP1A2*1 allele, CYP2B6 NM/RM and CYP2D6 NM/UM phenotypes (p<0.05 in the univariate analysis). ABCB1 C1236T T, C3435T T and G2677A/T A/T alleles were related to lower Cmax/DW compared to C, C and G alleles (p<0.05 in univariate and multivariate analysis). ABCB1 C1236T T allele was also related to lower AUC/DW (p<0.05 in multivariate analysis). The remaining studied transporter genes (ABCC2, SLC22A1 and SLCO1B1) and metabolizing enzyme genes (CYP3A5, CYP2C19, CYP2C9, CYP2C8, CYP3A4, CYP2A6 and UGT1A1) were unrelated to dexketoprofen pharmacokinetic variability. We conclude that dexketoprofen pharmacokinetics can be influenced by several polymorphisms, although there is not a clear pharmacogenetic predictor that would justify individualization of therapy based on its genotyping. Further studies should be conducted to confirm the role of SNPs in CYP2B6, CYP2D6, CYP1A2 and ABCB1 on the pharmacokinetic variability of dexketoprofen. Current evidence on dexketoprofen pharmacogenetics does not justify its inclusion in pharmacogenetic guidelines.